An enzyme immunoassay of ADAMTS13 distinguishes patients with thrombotic thrombocytopenic purpura from normal individuals and carriers of ADAMTS13 mutations - Zhou, Wenhua; Tsai, Han-Mou (Thrombosis and Haemostasis, 2004)
Recent studies demonstrate that assay of ADAMTS13, a circulating zinc metalloprotease that cleaves von Willebrand factor (VWF) at the Y1605-M1606 bond, is an important tool in the diagnosis of thrombotic thrombocytopenic purpura (TTP). In order to develop a method that could be adapted for general use, we describe an enzyme immunoassay (EIA)-based method for measuring the activity of ADAMTS13 in patient plasma samples. A monomeric peptide consisting of the amino acid residues D1596-R1668 of VWF was produced that spanned the ADAMTS13 cleavage site and was franked by glutathione s-transferase (GST) and a 6His sequences at the amino and carboxyl termini respectively. When probed with either anti-GST or anti-6His, the VWF fragment appeared as a 38.1-kDa band. After incubation with normal plasma, the VWF fragment was replaced by a 30.4-kDa band, which was recognized by antiGST but not by anti-6His, consistent with the expected cleavage at the Y1605-M1606 bond. EDTA or plasma samples from patients with TTP inhibited this cleavage. After incubation with normal plasma, the VWF fusion protein immobilized onto antiGST coated microtiter plate wells lost its anti-6His binding activity in a timeand plasma concentration-dependent manner. By using this EIA, the ADAMTS13 activity level was less than 0.12 U/mL in patients with acquired or hereditary TTP, distinguishing these patients from normal individuals or carriers of one copy of mutant ADAMTS13 allele. These results suggest the EIA method based on the VWF fusion protein is a simple but promising alternative for measuring ADAMTS13 activity.
Keywords: von Willebrand factor; ADAMTS13; metalloprotease; thrombotic thrombocytopenic purpura; enzyme immunoassay